An ultra-highly active Ir–Ru–B/CeO2 catalyst for hydrogen generation from hydrazine monohydrate. Issue 34 (18th August 2021) - Qiu, Yu-Ping; Wang, Wei-Zhen; Chen, Mu-Hua; Shi, Qing; Yang, Zhi-Qing; Wang, Ping
Abstract : The Ir70 Ru30 –B/CeO2 catalyst exhibited unprecedented activity and exceptionally high stability for promoting N2 H4 ·H2 O decomposition, hence representing a promising step toward the development of N2 H4 ·H2 O as a viable hydrogen carrier. Abstract : On-demand hydrogen generation from catalytic decomposition of hydrazine monohydrate (N2 H4 ·H2 O) represents a promising chemical hydrogen storage technology for onboard and portable applications. But the performances of existing catalysts are still far from meeting the requirements of practical applications. Herein, we report the synthesis of the Ir–Ru–B/CeO2 catalyst using a chemical reduction method followed by reductive annealing and its intriguing properties for catalyzing N2 H4 ·H2 O decomposition under alkaline conditions. Our study demonstrates that Ir–Ru alloying, B-doping and the strong metal–support interactions could collectively contribute to the catalytic performance. As a consequence, the Ir–Ru–B/CeO2 catalyst prepared under optimal conditions shows an unprecedented activity, which is over 4-fold higher than the best level of the state-of-the-art catalysts. Meanwhile, the catalyst exhibits high stability in cyclic usage, due presumably to its moderate binding strength with the intermediates/products of N2 H4 ·H2 O decomposition. To the best of our knowledge, this is the first report of a B-doped noble metal alloy catalyst for N2 H4 ·H2 O decomposition. Its impressive activity and stability may enlighten and encourage future exploration of high-performance catalysts for promoting the practical application of N2 H4 ·H2 O as a viable hydrogen carrier.